Pieter de Graeff (1638-1707) and his treffelyke bibliotheek : Exploring and Reconstructing an Early Modern Private Library as a Book Collection and as a Physical Space - Piccoli, Chiara, (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
On 9 July 1709, over 2,300 books were sold at a public auction at the shop of the publishing family Boom in Amsterdam. They comprised the 'beautiful library' ( treffelyke bibliotheek ) of the patrician Pieter de Graeff (1638-1707), member of a prominent regent family. This monograph draws on unpublished archival sources and De Graeff's book auction catalogue to explore his library and its significance. While tracing the microhistories of De Graeff's relatives against the backdrop of the Dutch Republic's unfolding history, this research reveals his book collection as a microcosmos of knowledge accumulated through generations. De Graeff's boeken kamer -- the library room in his Amsterdam residence - is also investigated and visualized through computer graphics, resulting in an online, interactive and annotated 3D model.